Population Distributions of Thymic Function in Adults: Variation by Sociodemographic Characteristics and Health Status. (3rd May 2016) - Feinstein, Lydia; Ferrando-Martínez, Sara; Leal, Manuel; Zhou, Xuan; Sempowski, Gregory D.; Wildman, Derek E.; Uddin, Monica; Aiello, Allison E.
ABSTRACT: The thymus is critical for mounting an effective immune response and maintaining health. However, epidemiologic studies characterizing thymic function in the population setting are lacking. Using data from 263 adults in the Detroit Neighborhood Health Study, we examined thymic function as measured by the number of signal joint T-cell receptor excision circles (sjTREC) and assessed associations with established indicators of physiological health. Overall, increasing age and male gender were significantly associated with reduced thymic function. Adjusting for covariates, individuals with elevated levels of the pro-inflammatory biomarkers C-reactive protein (β: −0.50 [95% CI: −0.82, −0.18] for moderate elevation, β: −0.29 [95% CI: −0.59, 0.00] for high elevation) and interleukin-6 (β: −0.60 [95% CI: −0.92, −0.28] for moderate elevation, β: −0.43 [95% CI: −0.77, −0.08] for severe elevation) also had lower thymic function. Compared to individuals with a BMI < 25, individuals who were overweight (β: 0.36 [95% CI: 0.07, 0.64]) or obese (β: 0.27 [95% CI: −0.03, 0.56]) had higher thymic function. Differences by self-rated health were not statistically significant. Our findings underscore demographic- and health-related gradients in thymic function among adult residents of Detroit, suggesting thymic function may be an important biomarker of health status in adults at the population level.